Comparison of rapid methods for detection of Giardia spp. and Cryptosporidium spp. (oo)cysts using transportable instrumentation in a field deployment - Keserue, H.A.; Fuchslin, H.P.; Wittwer, M.; Hung Nguyen-Viet; Nguyen, T.T.; Surinkul, N.; Koottatep, T.; Schurch, N.; Egli, T. (American Chemical Society, 2012)
Reliable, sensitive, quantitative, and mobile rapid screening methods for pathogenic organisms are not yet readily available, but would provide a great benefit to humanitarian intervention units in disaster situations. We compared three different methods (immunofluorescent microscopy, IFM; flow cytometry, FCM; polymerase chain reaction, PCR) for the rapid and quantitative detection of Giardia lamblia and Cryptosporidium parvum (oo)cysts in a field campaign. For this we deployed our mobile instrumentation and sampled canal water and vegetables during a 2 week field study in Thailand. For purification and concentrations of (oo)cysts, we used filtration and immunomagnetic separation. We were able to detect considerably high oo(cysts) concentrations (ranges: 15–855 and 0–240 oo(cysts)/liter for Giardia and Cryptosporidium, respectively) in 85 to 300 min, with FCM being fastest, followed by PCR, and IFM being slowest due to the long analysis time per sample. FCM and IFM performed consistently well, whereas PCR reactions often failed. The recovery, established by FCM, was around 30% for Giardia and 13% for Cryptosporidium (oo)cysts. It was possible to track (oo)cysts from the wastewater further downstream to irrigation waters and confirm contamination of salads and water vegetables. We believe that rapid detection, in particular FCM-based methods, can substantially help in disaster management and outbreak prevention.